1981
DOI: 10.1029/jc086ic06p05231
|View full text |Cite
|
Sign up to set email alerts
|

A case study relating high ground level ozone to enhanced photochemistry and isentropic transport from the stratosphere

Abstract: Exceptionally high ozone ground level concentrations (>200 ppb) observed in Denver, Colorado, on the afternoon of March 4, 1978, are explained in terms of enhanced photochemistry combined with isentropic transport of ozone from the stratosphere. The maximum ozone concentrations observed on March 4 is the highest recorded for the 1975-1978 period. Inspection of the local pollutant and meteorological data shows high early morning accumulation of precursor gases and enhanced potential for afternoon photochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Downward transport of ozone is shown to contribute significantly to ozone variations observed over alpine sites, the Himalayas, the Tibetan Plateau, western United States, and western Europe [e.g., Stohl et al, 2003;Ding and Wang, 2006;Langford et al, 2009;Kumar et al, 2010]. Though STT influences the ozone levels in the middle to upper troposphere occasionally, it can deeply penetrate down to the lower troposphere and can enhance near-surface ozone levels [Ludwig et al, 1977;Haagenson et al, 1981;Stohl et al, 2000;Cooper et al, 2005;Akriditis et al, 2010;Lin et al, 2012a].…”
Section: Introductionmentioning
confidence: 99%
“…Downward transport of ozone is shown to contribute significantly to ozone variations observed over alpine sites, the Himalayas, the Tibetan Plateau, western United States, and western Europe [e.g., Stohl et al, 2003;Ding and Wang, 2006;Langford et al, 2009;Kumar et al, 2010]. Though STT influences the ozone levels in the middle to upper troposphere occasionally, it can deeply penetrate down to the lower troposphere and can enhance near-surface ozone levels [Ludwig et al, 1977;Haagenson et al, 1981;Stohl et al, 2000;Cooper et al, 2005;Akriditis et al, 2010;Lin et al, 2012a].…”
Section: Introductionmentioning
confidence: 99%
“…Stratospheric intrusions have long been linked to short‐lived increases in surface O 3 [ Chung and Dann , 1985; Haagenson et al , 1981; Mukammal et al , 1985; Viezee et al , 1983], particularly at higher elevations [ Ambrose et al , 2011; Davies and Schuepbach , 1994; Langford et al , 2009a; Stohl et al , 2000]. The importance of STT as a source for surface O 3 remains highly uncertain, however.…”
Section: Introductionmentioning
confidence: 99%
“…It is then transported towards the equator by baroclinic waves and is folded into the atmosphere by amplifying vortices. Other investigators (Wolff et al, 1977;Haagenson, 1981;Husian et al, 1977) have confirmed these observations. …”
supporting
confidence: 77%